Naphthazarin modified carbon paste electrode for determination of copper(II) - Chaisuksant R. (2014)
A carbon paste electrode modified with naphthazarin (5,8-dihydroxy-1,4- naphthoquinone) was fabricated as a copper(II) sensor. Voltammetric and potentiometric detections were investigated. Adsorptive stripping voltammetry offers better sensitivity but poorer repeatability than potentiometry. The applied potential and current passing in voltammetric detection cause irreversible electrode reactions and shortening of the lifetime of the electrode. Potentiometric determination in batch and flow injection using 3% (w/w) of naphthazarin in the paste exhibited linear response with supra-Nernstian slope to copper(II) over a wide concentration range of three orders of magnitude in 0.10 M ammonium acetate medium. The potentiometric detection limits were 1.5 × 10-6 and 3.0 × 10 -5 M by batch and flow injection, respectively. The electrode shows a good selectivity for copper(II) over a wide variety of metal ions and was applied to the analysis of alloys. The electrode response time was 50 sec and it showed good reproducibility for at least 60 days. © 2007 Springer-Verlag.